2013
DOI: 10.1016/j.jprot.2013.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and metabolomic responses in hepatopancreas of Mytilus galloprovincialis challenged by Micrococcus luteus and Vibrio anguillarum

Abstract: The outbreak of pathogens can induce diseases and lead to massive mortalities of aquaculture animals including fish, mollusk and shrimp. In this work, the responses induced by Micrococcus luteus and Vibrio anguillarum were investigated in hepatopancreas of mussel Mytilus galloprovincialis using proteomics and metabolomics. Metabolic biomarkers demonstrated that M. luteus and V. anguillarum injections could induce osmotic stress and disturbance in energy metabolism. And the uniquely and more markedly altered me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 61 publications
2
47
0
Order By: Relevance
“…Both ubiquitin thioesterase and ubiquitin are regulatory proteins involved in the nonlysosomal degradation of intracellular proteins related to apoptosis induced by stressors [22]. In addition, ubiquitin-related proteins are responsive to immune and oxidative stress, which was observed in bacterial challenged mussel M. galloprovincialis and acute free radical-treated mussel Mytilus edulis [23,24]. Ribosomal proteins perform the crucial function of protein biosynthesis and have been also recognized as immunogenic proteins [23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both ubiquitin thioesterase and ubiquitin are regulatory proteins involved in the nonlysosomal degradation of intracellular proteins related to apoptosis induced by stressors [22]. In addition, ubiquitin-related proteins are responsive to immune and oxidative stress, which was observed in bacterial challenged mussel M. galloprovincialis and acute free radical-treated mussel Mytilus edulis [23,24]. Ribosomal proteins perform the crucial function of protein biosynthesis and have been also recognized as immunogenic proteins [23].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, ubiquitin-related proteins are responsive to immune and oxidative stress, which was observed in bacterial challenged mussel M. galloprovincialis and acute free radical-treated mussel Mytilus edulis [23,24]. Ribosomal proteins perform the crucial function of protein biosynthesis and have been also recognized as immunogenic proteins [23]. RNA polymerase II is responsible for the transcription of genes coding for protein in the nucleus [25].…”
Section: Resultsmentioning
confidence: 99%
“…With the development of system biology techniques (genomics, transcriptomics, proteomics and metabolomics), researchers have applied these eomic approaches to fish and shellfish immunology, which can provide a comprehensive understanding of immune responses of marine aquaculture animals to pathogen challenges [11,12]. Recently, Ji et al reported the proteomic responses in M. galloprovincialis challenged by another vibrio, V. anguillarum [12].…”
Section: Introductionmentioning
confidence: 99%
“…As an immune organ, the digestive gland of marine bivalves is the most frequently used organ in immunity studies due to the filter-feeding habit of M. galloprovincialis [8,11,13]. The organ of gill can be directly attacked by marine pathogens and has been also investigated in shellfish immunology [12,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Succinate is a tricarboxylic acid cycle (TCA) intermediate and is capable of donating electrons to the electron transport chain via oxidation to fumarate by succinate dehydrogenase (SDH). Decreased expression of SDH and increased levels of succinate are indicative of oxidative stress in shellfish when oxygen availability is limited (Tuffnail et al 2009 ;Anestis et al 2010 ;Connor and Gracey 2012 ), and when organisms are exposed to toxins (Wu et al 2013a ;Hanana et al 2014 ) or pathogens (Ji et al 2013 ;Wu et al 2013b ). Elevated tissue concentrations of succinate are also indicative of poor larval quality due to lower capacity for energy production (Young et al 2015b ).…”
Section: Discussionmentioning
confidence: 99%